2020
DOI: 10.3168/jds.2019-17420
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characterization of Staphylococcus aureus isolates from subclinical bovine mastitis in southern Xinjiang, China

Abstract: Staphylococcus aureus is one of the major pathogens causing mastitis in dairy herds. The colonization of dairy cows and subsequent contamination of raw milk by S. aureus, especially strains exhibiting multidrug resistance and biofilm-forming and toxin-producing abilities, remains an important issue for both dairy farmers and public health. In this study, we investigated the prevalence, antimicrobial susceptibility, biofilm formation, and genetic diversity of S. aureus from subclinical bovine mastitis in dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
42
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 46 publications
(88 reference statements)
11
42
3
2
Order By: Relevance
“…Bovine mastitis is a major disease of dairy cows, which has a great impact on the dairy industry and brings significant economic losses (Hata et al 2010;Li et al 2017;Wolf et al 2011;Zaatout et al 2020). S. aureus is the most frequently recovered pathogen from mastitis cases (Hata et al 2010;Ote et al 2011;Ren et al 2020), and responsible for subclinical and persistent intramammary infections. Multiple studies reported the diversity of genotype and phenotype of S. aureus strains obtained from bovine mastitis (Haveri et al 2005;Suleiman et al, 2018;Piccinini et al 2012;Ronco et al 2018;Veh et al 2015).…”
Section: Bovine Mastitis and Endometritismentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine mastitis is a major disease of dairy cows, which has a great impact on the dairy industry and brings significant economic losses (Hata et al 2010;Li et al 2017;Wolf et al 2011;Zaatout et al 2020). S. aureus is the most frequently recovered pathogen from mastitis cases (Hata et al 2010;Ote et al 2011;Ren et al 2020), and responsible for subclinical and persistent intramammary infections. Multiple studies reported the diversity of genotype and phenotype of S. aureus strains obtained from bovine mastitis (Haveri et al 2005;Suleiman et al, 2018;Piccinini et al 2012;Ronco et al 2018;Veh et al 2015).…”
Section: Bovine Mastitis and Endometritismentioning
confidence: 99%
“…Further, 161 isolates possessed at least 2 SAg genes (Katsuda et al 2005;Hata et al 2006). S. aureus strains isolated from bovine mastitic milk were separated into 60 patterns and 16 lineages by pulse field gel electrophoresis, and the most common combinations of toxin genes were sec, seg, sei, sel, and tst; or seg and sei; or sec, seg, sei, sel, sen and tst (Hata et al 2010;Hoekstra et al 2020;Li et al 2017;Ren et al 2020). The predominant isolate possessed SAg toxin genes supporting the theory that SAg toxins are important for udder pathogenesis of bovine mastitis.…”
Section: Bovine Mastitis and Endometritismentioning
confidence: 99%
“…Ribeiro et al (2009) in a study on pathogenic microorganisms in bovine milk, found the highest resistance rates of 53.5% when the strains ISSN 2166-0379 2020 were submitted to penicillin. Similarly, Ren et al (2020) investigated the prevalence and antimicrobial susceptibility of Staphylococcus aureus from subclinical bovine mastitis in dairy farms located in China. The authors found the resistance rates to penicillin, tetracycline, and chloramphenicol were 58.5, 18.5, and 1.5%, respectively.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…Several characteristics contribute to the pathogenesis and spread of S. aureus, including virulence factors, host, and environment (ACOSTA et al, 2018). Its ability to adhere and form biofilms on biotic and abiotic surfaces significantly increases the persistence of this pathogen in equipment and facilities, providing a physiological advantage as an etiological agent of diseases caused by food consumption, especially through the consumption of milk and its derivatives (MERGHNI et al, 2015;WANG et al, 2018;REN et al, 2020) The formation of biofilms contributes to the resistance to antimicrobials (MELCHIOR et al, 2006;RAZA et al, 2013). Moreover, the excessive use of antimicrobials has been shown to favor the emergence and selection of resistant bacteria, altering the structure of bacterial communities and inducing a rapid evolution, with unpredictable consequences for human and animal health (VAZ-MOREIRA; NUNES; MANAIA, 2014).…”
Section: Introductionmentioning
confidence: 99%